Fuzzy Application In Decision Support System In The Senior High School Selection In Bandar Lampung - Wijaya, Robin (Prosiding International conference on Information Technology and Business (ICITB), 2017)
Determining the best and the best school is not easy. we should look for information in the schools we attend, then compare them and choose which schools fit the criteria. One expert system design to predict the right school using the Fuzzy Inference System Tsukamoto method which includes 3 variables: academic value, parent income, and school. As a result, the inference output of each rule is given explicitly (crisp) based on the Î±-predicate (fire strength). The final result is obtained by using weighted average. Fuzzy inference system with Tsukamoto process is used to solve an unstructured problem simply. so by applying the method, can get the right school choice statement.Â Keywords: Fuzzy Inference System, and Tsukamoto.